Savage lands - Clark, Clare (Houghton Mifflin Harcourt, 2010)
In 1704 the French colony of Louisiana needs wives for the struggling settlers and Elisabeth and twenty-three other girls are dispatched to satisfy the request. The skeptical bride soon falls in love with her charismatic and ruthlessly ambitious soldier-husband, Jean-Claude, a passion which is shared by an abandoned cabin boy, Auguste, who has also fallen under the spell of the dashing Jean-Claude. When in time Jean-Claude betrays them both, the two find themselves bound together in ways they never anticipated.